Disentangling genetic from environmental effects on phenotypic variability of southern rock lobster (Jasus edwardsii) postlarvae. Issue 11 (16th November 2022) - Villacorta‐Rath, Cecilia; Green, Bridget S.; Gardner, Caleb; Murphy, Nick P.; Souza, Carla A.; Strugnell, Jan M.
Abstract: Environmental conditions experienced during the larval dispersal of marine organisms can determine the size‐at‐settlement of recruits. It is, therefore, not uncommon that larvae undergoing different dispersal histories would exhibit phenotypic variability at recruitment. Here, we investigated morphological differences in recently settled southern rock lobster ( Jasus edwardsii ) recruits, known as pueruli, along a latitudinal and temporal gradient on the east coast of Tasmania, Australia. We further explored whether natural selection could be driving morphological variation. We used double digest restriction site‐associated DNA sequencing (ddRADseq) to assess differences in the genetic structure of recently settled recruits on the east coast of Tasmania over 3 months of peak settlement during 2012 (August–October). Phenotypic differences in pueruli between sites and months of settlement were observed, with significantly smaller individuals found at the northernmost site. Also, there was a lack of overall genetic divergence; however, significant differences in pairwise FST values between settlement months were observed at the southernmost study site, located at an area of confluence of ocean currents. Specifically, individuals settling into the southernmost earlier in the season were genetically different from those settling later. The lack of overall genetic divergence in the presence of phenotypic variation indicates that larval environmental history during the dispersal of J. edwardsii could be a possible driver of the resulting phenotype of settlers. Abstract : We found that Jasus edwardsii settlers exhibit phenotypic variability across a geographical and temporal gradient; however, this is not correlated with genetic divergence. Given the protracted pelagic larval duration of the species, we hypothesize that dispersal history drives phenotypic variability in this species.